Síntesis y caracterización de complejos de níquel y cobalto (II), sostenidos en ligandos derivados de 1H-pirazol para la sensibilización de TiO2 y su aplicación en fotocatálisis heterogénea empleando luz visible (2017)
The objective of this degree work is to synthesize complexes of nickel and cobalt (II) contained in ligands of 1H-pyrazole to sensitize TiO2 in order to achieve photocatalytic activity under visible radiance, in this way, the dichloro [bis (3,5-dimethyl-pyrazolyl) methane-NN] nickel (II) and dichloro [bis (3,5-dimethyl-pyrazolyl) methane-NN] cobalt (II) complexes were synthesized with the bis (3,5-dimethyl-1-pyrazolyl) methane ligand, the complexes were characterized by thermogravimetry, elemental analysis and infrared spectrum.